Effective control of a suspected cyromazine‐resistant strain of Lucilia cuprina using commercial spray‐on formulations of cyromazine or dicyclanil. Issue 10 (29th August 2014) - Baker, KE; Rolfe, PF; George, AJ; Vanhoff, KJ; Kluver, PF; Bailey, JN
<x xml:space="preserve">Abstract</x> Objective To demonstrate the protection of Merino sheep from flystrike by Lucilia cuprina with cyromazine or dicyclanil in an implant study and in the field. Methods In the implant study, sheep were treated with cyromazine or dicyclanil and implanted with 1st‐stage larvae from a newly isolated field strain of L. cuprina (CYR‐LS) or a reference strain (DZR50), then assessed over 3 days and compared with the implants on untreated control sheep. In the field study, weaner lambs were treated with cyromazine or dicyclanil and monitored weekly for flystrike over 18 weeks of grazing on the same farm from which the L. cuprina were isolated. Results Implant study: cyromazine (6%) provided effective protection against CYR‐LS and DZR50 L. cuprina for a minimum of 13 and 10 weeks, respectively. Dicyclanil (5%) provided at least 18 weeks' protection against both strains. Field study: only 1 of 386 lambs in the cyromazine‐treated group was struck in the first 14 weeks of the trial. No strikes occurred in the 198 sheep treated with dicyclanil (5%). Rainfall, temperature and flytrap data indicated consistent fly pressure during the study. Conclusions Based on the results of these studies, there was no evidence of reduced susceptibility to cyromazine or dicyclanil and the periods of protection of sheep against L. cuprina were unaffected and consistent with the registered label claims.